2018
DOI: 10.1111/jora.12349
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Family Aggression, Externalizing Behavior, and the Structure and Function of the Amygdala

Abstract: Using longitudinal data from 21 adolescents, we assessed family aggression (via mother, father, and youth report) in early adolescence, externalizing behavior in mid-adolescence, and magnetic resonance imaging (MRI) data in late adolescence. Amygdalae were manually traced, and used as seed regions for resting state analyses. Both family aggression and subsequent externalizing behavior predicted larger right amygdala volumes and stronger amygdala-frontolimbic/ salience network connectivity and weaker amygdala-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Notably, neural synchrony among mothers and adolescents was associated with less stress in youth. Saxbe et al (2018) examined family aggression and adversity. Using longitudinal data, they found that family aggression and externalizing behavior were predicted by differences in amygdala volumes and amygdala connectedness.…”
Section: Social Relationships and Brain Functionmentioning
confidence: 99%
“…Notably, neural synchrony among mothers and adolescents was associated with less stress in youth. Saxbe et al (2018) examined family aggression and adversity. Using longitudinal data, they found that family aggression and externalizing behavior were predicted by differences in amygdala volumes and amygdala connectedness.…”
Section: Social Relationships and Brain Functionmentioning
confidence: 99%
“…Saxbe et al. () and K. H. Lee, Oppenheimer, et al. () describe how structural and functional brain development may be implicated in the links between hostile family and peer environments with internalizing and externalizing symptomatology.…”
Section: The Interaction Between Brain Development and The Social Envmentioning
confidence: 99%
“…The articles in this special section nicely exemplify the strengths of applying neuroscience to psychopathology, as adolescence is a period at which many of these problems manifest themselves. All of the articles focus on patterns of functional activation associated with potential emotional and behavioral difficulties, including externalizing and conduct disorder behaviors (Brieant et al, 2018;Saxbe et al, 2018;Schriber et al, 2018;Trucco, Cope, Burmeister, Zucker, & Heitzeg, 2018), risky decision making (Hansen, Thayer, Feldstein-Ewing, Sabbineni, & Bryan, 2018;Rodrigo, Padr on, de Vega, & Ferstl, 2018), stress responsivity (T.-H. Lee, Qu, & Telzer, 2018), and depression symptomatology (K. H. Lee, Oppenheimer, et al, 2018). Recent calls have been made to build upon these insights and expand the field's scope to understanding normative processes, puberty, and the unique opportunities for positive development afforded by brain development during adolescence (Crone & Dahl, 2012;Pfeifer & Blakemore, 2012).…”
Section: An Integrative Approach That Incorporates Both Typical and Amentioning
confidence: 99%
See 2 more Smart Citations